Literary Works as Testimony to Non-Indifference: On the Pedagogical "Shading" of Janusz Korczak's Oeuvre - Agnieszka Cybal-Michalska (Jagiellonian University Press, 2024)
Each epoch leaves its own literary mark. The discourse of humanities concerning literary works as a reception of historically transformed social reality and socio-cultural experiences should include a reflection on the testimony of (non) indifference. The presentation referring to the pedagogical "shading" of Janusz Korczak's works will be a pretext for considering literature as a testimony of presence in social experiences but will also direct cognitive interests towards behaviour and interpersonal relations. Thus, analyses of the social conditions that resulted in Janusz Korczak's literature and, above all, reflections on what social effects it caused and continues to cause are cognitively fascinating. Thus, by embedding literature as a cultural feature in a network of social relations, it is worth reflecting on the type, not only of knowledge, but of psychological predispositions that can be reproduced in it, taking the quality of socio-cultural reality as a point of reference.